East Atlantic Pattern Drives Multidecadal Atlantic Meridional Overturning Circulation Variability during the Last Glacial Maximum - Song, Zhaoyang; Latif, Mojib; Park, Wonsun (Geophysical Research Letters, 2019)
The variability of the Atlantic Meridional Overturning Circulation (AMOC) and its governing processes during the Last Glacial Maximum (LGM) is investigated in the Kiel Climate Model (KCM). Under LGM conditions, multidecadal AMOC variability is mainly forced by the surface heat flux variability linked to the East Atlantic pattern (EAP). In contrast, the multidecadal AMOC variability under preindustrial conditions is mainly driven by the surface heat flux variability associated with the North Atlantic Oscillation (NAO). Stand‐alone atmosphere model experiments show that relative to preindustrial conditions, the change in AMOC forcing under LGM conditions is tightly linked to the differences in topography. Key Points Multidecadal AMOC variability during the LGM and its associated physical processes have been investigated by means of a climate model Multidecadal AMOC variability during the LGM is mainly driven by surface heat flux variability linked to the East Atlantic pattern as opposed to the North Atlantic Oscillation under preindustrial conditions Change in topography during the LGM is responsible for the change in AMOC forcing